The Role of Marketing Mix, Corporate Image and Brand Equity in Purchase Decision of Daihatsu Ayla - David Gunawan (Soegijapranata Catholic University, 2020)
The purpose of this research was to understand the influence of marketing mix, corporate image, and brand equity on decision to purchase Daihatsu Ayla from PT Astra International, Tbk – Daihatsu Sales Operation, Branch of Majapahit Semarang. The results indicated that the three variables significantly influence purchase decision dan corporate image was the variable with the strongest influence. It was also found that corporate image and brand equity are the moderating variables for marketing mix in influencing purchase decision of Daihatsu Ayla. The company can use the results for creating programs intended to strengthen corporate image and brand equity that will strengthen the influence of marketing mix on decision to purchase Daihatsu Ayla